If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(x + -7) + -8(x + 3) = 30 + -1x Reorder the terms: 10(-7 + x) + -8(x + 3) = 30 + -1x (-7 * 10 + x * 10) + -8(x + 3) = 30 + -1x (-70 + 10x) + -8(x + 3) = 30 + -1x Reorder the terms: -70 + 10x + -8(3 + x) = 30 + -1x -70 + 10x + (3 * -8 + x * -8) = 30 + -1x -70 + 10x + (-24 + -8x) = 30 + -1x Reorder the terms: -70 + -24 + 10x + -8x = 30 + -1x Combine like terms: -70 + -24 = -94 -94 + 10x + -8x = 30 + -1x Combine like terms: 10x + -8x = 2x -94 + 2x = 30 + -1x Solving -94 + 2x = 30 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -94 + 2x + x = 30 + -1x + x Combine like terms: 2x + x = 3x -94 + 3x = 30 + -1x + x Combine like terms: -1x + x = 0 -94 + 3x = 30 + 0 -94 + 3x = 30 Add '94' to each side of the equation. -94 + 94 + 3x = 30 + 94 Combine like terms: -94 + 94 = 0 0 + 3x = 30 + 94 3x = 30 + 94 Combine like terms: 30 + 94 = 124 3x = 124 Divide each side by '3'. x = 41.33333333 Simplifying x = 41.33333333
| 4x^5-32x^3=0 | | -4x+11=14 | | x=16*4x | | 75=20x-15y | | 75=20x+15y | | F(x)=cos(8x-1) | | 58=17x-7y | | 58=17x+7y | | x=15-(13-19) | | x=(x+1)*(1-2x) | | x=(2x+1)*2 | | x=(12x-6)/3 | | x=7*(-x+2) | | 3/4*s=-20 | | S3/4=-20 | | x(x+8)=6x+3 | | 5x+4-3x=7x-8+11 | | y-2=1/2(x-(-4)) | | 218-178= | | 6x^3+15X^2+6x=0 | | 46.37*18.48= | | 2xy*x+3y= | | 6(x^2)+6x-44=0 | | 5(2x-6)=2(5-x) | | 3+4=-5+2 | | 3x+2=-5x+4 | | 4*(3+4x)=-18 | | 12d+7=6d+31 | | 13x+15-(x+2)= | | 5(a+7)=38 | | 47.2=9c-5 | | y=kx+10 |